The impact of information technology on supply chain management - Owen Mutebezi Joshua (Uganda Christian University, 2024)
SCM has been described as one of the most thriving management domain, which assists enterprises in enhancing their supply chain processes (Graham2013). The tendency of supplying computing and communication capability in common SCM solutions is auxiliary to increasing associated business intelligence focused on enhancing management decisions towards addressing the flow of the supply chain network so as to become competitive, sustaining higher levels of service with less inventory, containing supply chain’s costs and managing electronic threats (Graham2013). This recent years, many people have witnessed the emergence of solutions of problems when applying Information technology in supply chain management because such innovations are enabled by Information technology which changes the competitiveness of firms in the supply chain management (Waters 2009). Particularly, the using of the information technologies has been significantly focused in the supply chains where the interrelationship of material, information and finance flows among the customers, suppliers, manufacturers and distributors network takes place (Lee 2014). Nonetheless, up to now, the connection between the two concepts depends on the internal aspects of IT utilization in SCM still remains poorly explored. So, in this paper, the impact which information technology (IT) had on the SCM of Jumia Uganda was evaluated. The study also aimed at determining other areas of IT use in supply chains. Descriptive and analytical was the nature of research. This is where data has been quantified, tabulating findings, and understanding treatment of information on respectively. The sample size is composed of 52 respondent from IT department, marketing, logistics, finance department, and procurement department. Data was obtained from the field using questionnaires and later analyzed using SPSS. Findings show that IT has improved the processes of the transactions across the various functions and also is integrated in such a way that information flows along the various functions between procurement, logistics, and marketing. The various technologies used have reduced the operations cost in the supply chain; hence, a lot of savings has been achieved. It is also noted that lead time for orders have reduced due to effective sharing of information. There has an improved customer services where both internal and external customers are happy in due to faster response from the supply chain as supported by Lim and Palvia, 2011. The study suggests that manufacturing organizations should incorporate IT in the supply chains in order to enhance efficiencies. In addition, the study suggests that manufacturing firms in Uganda need to apply all components of information technology in the system Evans et al. (1993), and this will allow the organization to enhance the general performances of the supply chain